Effects of perioperative anesthetics on the postoperative prognosis of patients undergoing surgery for cervical cancer - Deng, Linyan; Wang, Tingting; Zhang, Qiaofeng; Shu, Shaofang; Chen, Xiangdong (Frontiers in Pharmacology, 2025)
Cervical cancer is a common malignancy among women, and tumor excision is the most common surgical intervention. Anesthetics used during surgery include general intravenous, volatile, local anesthetics, sedative and analgesic. Studies have shown that the selection of perioperative surgical methods and anesthetics may influence postoperative metastasis and cancer recurrence through their effects on the immune response and tumor cells. Therefore, the selection of perioperative anesthetic has a significant impact on patients undergoing surgery for cervical cancer. This study summarizes the effects and related mechanisms of common anesthetics on the prognosis of patients undergoing surgery for cervical cancer to provide a basis for developing more optimal anesthesia protocols.